Have they pinched it from another newspaper? - Monica Reichenberg; Ingela Wadbring (Stockholm University Press, 2008)
This article presents an intervention study where two conditions of reading instruction are compared. In a base condition four teachers-two in the experimental groups and two in the control groups-and their students in grade 5 discuss newspaper texts during a regular lesson. The majority of the students were poor comprehenders. In the intervention condition, the teachers in the experimental groups used a model of structured text talk, Questioning the Author (QtA), after repeatedly having participated in seminars led by the investigators where the model was practised. During the regular lessons the four teachers mostly asked questions to check if the students know the meaning of difficult words. The students made few inferences and reflections. During the QtA lessons the teachers' question types had undergone a change. There was a dramatical increase in the number of inference- and half-open questions and the students made numerous inferences, reflections and initiated own questions. This was not the case in the control groups.